Making schools more effective : report of the Australian effective schools project - Piper, Kevin.; Banks, Diana.; Evans, Beryl.; McGaw, Barry. (Australian Council for Educational Research, 1992)
The effective schools project. Keys to school effectiveness. The curriculum in effective schools. Staff in effective schools. Parents in effective schools...